The advent of beauty Mannequins: strategic appropriation of feminine beauty in Bhattacharjya's Mannequins - Pillai, Rachana S; Sreenivasulu, Yadamala (Penerbit Universiti Kebangsaan Malaysia, 2024)
The glamour industry is an intersection where female empowerment parallels female objectification. The industry offers individuals an exclusive platform for exploring their inner beauty, owning their gender, and having financial independence. However, it has set many unrealistic beauty standards and myths, which the models constantly strive to achieve. This compels them to succumb to beauty demands, thus increasing the rates of plastic surgery and fat loss treatments. Capitalist giants take advantage of the tension between natural and ideal beauty, making huge profits out of the mental game. The middle ground is to strategically appropriate these beauty standards and femininity in favour of women to accomplish the more prominent targets of financial independence, social status, and individual identity. The present paper analyses the shift in women's strategy with reference to Manjima Bhattacharjya's Mannequins, which voice the emergence of a new generation of working women in India's glamour industry. This study explores how a woman's journey of empowerment in the Indian fashion industry diverts into a continuous process of commodification, obsession, and exploitation. It further attempts to view the platform of the glamour industry as a possible opportunity for women to strategically unite, own, and rule the social system, followed by analysing the present situation of the industry through a postfeminist lens. Finally, it connects how capitalist industries trigger this toxic version of beauty standards, which overshadows the immense opportunities that the glamour industry offers to women in both urban and global spaces.